Sistem Monitoring Pekerjaan Proyek Menggunakan Metode Extreme Programming - Prayoga, Mohamad Adrian; Huizen, Lenny Margaretta; Asmiatun, Siti (Journal of Information System Research (JOSH), 2024)
Government agencies such as the Office of Public Works (PU) Bina Marga and Cipta Karya (BMCK) are in charge of managing and carrying out projects related to housing and road infrastructure development, maintenance, and oversight. There is a need to keep an eye on the road infrastructure projects going on at the Public Works Office of Bina Marga and Cipta Karya. Road building is slowed down, complicated, and prone to mistakes since the Public Works Office of Highways and Human Settlements does not yet have a framework in place to enable monitoring. The goal of this study is to develop a method for tracking road building progress that will make the process easier and faster. One development approach that streamlines the many phases of development to make it more adaptable and flexible is the Extreme Programming technique. This system is designed using UML(Unified Modeling Language) as a means to analyze and design the system. The test results using the Technology Acceptance Model (TAM) resulted in a value of 92.33%, which is considered very good and has met the expected criteria.